Estruturas causativas em Tenetehára: uma abordagem minimalista - Quesler Fagundes Camargos (2013)
My aim in this dissertation is to investigate the causative structures in Tenetehára. In descriptive terms, it is shown that this language displays two causative morphemes: {mu-} and {-(u)kar}. The prefix {mu-} main role is to causativize inergative and unaccusative predicates, whereas the suffix {-(u)kar} causativizes transitive verbs. Following Pylkkänens (2002, 2008) proposal, I hypothesize that Voiceo and voCAUSE are separate pieces in the Tenetehára inventory of functional heads. I also demonstrate that they cannot be grouped together into a unique morpheme in the lexicon. This hypothesis is based on the fact that these heads are morphologically realized in Tenetehára. Thus, when a causative transitive receives the reflexive morpheme {ze-}, this is an indication that the Voiceo is overtly realized. I also propose that the causative head is realized by the morpheme {mu-}. In line with this reasoning, my proposal is that both Voiceo and voCAUSE are separate heads in the verbal argument structure. Moreover, the voCAUSE head could be introduced without the projection of VoiceP. This proposal is based on the fact that there occurs a situation in which the causative construction does not introduce an agent/external argument. This occurs in particular when there is an applied argument introduced by an applicative head above vPCAUSE. This proposal is corroborated by the realization of a high applicative head, which is morphologically instantiated by the morpheme {eru-} above voCAUSE. Based upon Pylkkänens (2002, 2008) morphosyntactic diagnostics, I show that the causative {mu-} only selects root. This proposal is evidenced by the following diagnostics: the impossibility of verbal morphology between the root and the causative head; (ii) the fact that manner-adverbs cannot scope over the root. As to the morpheme {-(u)kar}, the proposal is that it only selects a phasic vP. This hypothesis is reinforced by the following diagnostics: (i) there is no restriction of verbal morphology between the root and the causative verb (including high applicative morphology), (ii) the causative allows lower scope for agentive adverbial modification inside voCAUSE head.